A Cost-Benefit Analysis Model Based on NPV Methods and Full Life Cycle of Land Use Projects. Issue 5 (February 2020) - Qi, Xin; Li, Xinye; Jin, Jinghua
Abstract: If you realize that your sweet house will damage the ecosystem, you must be amazed. In fact, most land use projects around us affect ecosystem services directly and even result in environmental degradation. The environmental cost has caused a reduction in economic benefits presumably, nonetheless, which has never attracted enough academic attention. To show the real economic cost of land use projects, we establish an ecological services valuation model based on the governance cost method. When assessing the environmental costs caused by pollution, we evaluate the paid economic costs for the pollution control and the virtual cost that should have been paid for pollution abatement. When assessing the costs caused by non-pollution factors, we compute the economic value of regional ecosystem service value according to Costanza indicator system and the value of localized carbon storage and carbon sequestration based on the INVEST model.